2015
DOI: 10.1021/acs.jmedchem.5b00709
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Based Design of a Small Molecule CD4-Antagonist with Broad Spectrum Anti-HIV-1 Activity

Abstract: Earlier we reported the discovery and design of NBD-556 and their analogs which demonstrated their potential as HIV-1 entry inhibitors. However, progress in developing these inhibitors has been stymied by their CD4-agonist properties, an unfavorable trait for use as drug. Here, we demonstrate the successful conversion of a full CD4-agonist (NBD-556) through a partial CD4-agonist (NBD-09027), to a full CD4-antagonist (NBD-11021) by structure-based modification of the critical oxalamide midregion, previously tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
119
0
9

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 60 publications
(132 citation statements)
references
References 87 publications
4
119
0
9
Order By: Relevance
“…The x-ray structure of NBD-11021 bound to HIV-1 gp120 confirmed that this molecule binds to the Phe43 cavity 18 but in a slightly different orientation than we observed with NBD-556 and other partial antagonists such as NBD-09027 so that the piperidine “N” forms a H-bond with Asp368, a critical interaction that was missing in all our compounds so far. The wide breadth of anti-HIV-1 activity profile of NBD-11021 against a large panel of HIV-1 pseudoviruses representing diverse subtypes of clinical isolates and availability of its structural information in complex with gp120 motivated us to continue the design of more robust and active analogs of this molecule.…”
Section: Introductionsupporting
confidence: 65%
See 3 more Smart Citations
“…The x-ray structure of NBD-11021 bound to HIV-1 gp120 confirmed that this molecule binds to the Phe43 cavity 18 but in a slightly different orientation than we observed with NBD-556 and other partial antagonists such as NBD-09027 so that the piperidine “N” forms a H-bond with Asp368, a critical interaction that was missing in all our compounds so far. The wide breadth of anti-HIV-1 activity profile of NBD-11021 against a large panel of HIV-1 pseudoviruses representing diverse subtypes of clinical isolates and availability of its structural information in complex with gp120 motivated us to continue the design of more robust and active analogs of this molecule.…”
Section: Introductionsupporting
confidence: 65%
“…The basic synthesis routes to make this series of NBD-compounds have been previously reported 18 . First, we prepared imine 2 from racemic pipecolic acid and racemic tert -butanesulfinamide ( Scheme 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This study is expected to good step for new ways of designing more strong and effective HIV-1 entry inhibitors. As suggested from the x-ray structure of NBD-11021, it bounds to HIV-1 env gp120 and gives rise to a conclusion that this molecule binds to the Phe43 cavity 14 . The energetic contribution of each amino acid was verified at the binding site involved in stabilizing the complex, ( PDB: 5U6E) 15 …”
Section: Introductionmentioning
confidence: 99%